2021
DOI: 10.1111/jog.15010
|View full text |Cite
|
Sign up to set email alerts
|

Attitude changes toward prenatal testing among women with twin pregnancies after the introduction of noninvasive prenatal testing: A single‐center study in Japan

Abstract: Aim: This study aimed to evaluate changes in prenatal testing among women with twin pregnancies before and after the introduction of noninvasive prenatal testing (NIPT). To date, no consensus on prenatal testing for twin pregnancies has been reached in Japan. Methods: Women pregnant with twins who requested prenatal testing at Kyushu Medical Center from 2005 to 2018 were included in this study. Genetic counseling was provided to all participants. Their chosen methods of testing were collected and classified as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…NIPT has been used in the prenatal detection of twins for many years, and its detection ability has also been clinically recognized to some extent. In Japan, more women with twin pregnancies tend to choose to undergo NIPT, especially those who conceive through assisted reproductive technology (ART) 28 . Fosler et al 29 reported the detection of trisomy 21 by cell-free fetal DNA (cff-DNA)-based whole-genome sequencing (WGS) NIPT in twin pregnancies and found that its performance was almost the same as that in singleton pregnancies, with a very low overall false-positive rate.…”
Section: Discussionmentioning
confidence: 99%
“…NIPT has been used in the prenatal detection of twins for many years, and its detection ability has also been clinically recognized to some extent. In Japan, more women with twin pregnancies tend to choose to undergo NIPT, especially those who conceive through assisted reproductive technology (ART) 28 . Fosler et al 29 reported the detection of trisomy 21 by cell-free fetal DNA (cff-DNA)-based whole-genome sequencing (WGS) NIPT in twin pregnancies and found that its performance was almost the same as that in singleton pregnancies, with a very low overall false-positive rate.…”
Section: Discussionmentioning
confidence: 99%